The Effect of Product Quality, Brand Trust, Price and Sales Promotion on Purchase Decisions on Royal Residence Surabaya (Case Study in PT. Propnex Realti Visit) - Yuni Rahmawati; Sengguruh Nilowardono (IJESEMS : International Journal of Engineering Science Educatioon and Management System, 2018)
This study aims to explore the decision to purchase Royal Residence Housing products in Surabaya. Exploration of Royal Residence Housing products is carried out using quantitative research methods.Data testing is done by questionnaires analyzed using statistical analysis such as validity and reliability tests and multiple linear regression analysis with the help of SPSS 21.0 for Windows.The results showed that the independent variable (product), product quality, brand trust, price and promotion simultaneously had an effect on the dependent variable, namely the purchase decision to produce conclusions, that is, accepted. This is evidenced by the significance value of 0.000 or less than 0.05 and the value of Fcount (61.441)> Ftable (2.71). There is a significant and not significant partial effect of the independent variable on the dependent variable. Through the results of calculations that have been done with a significant level of results of 0.000 is smaller than 0.05.